2022
DOI: 10.3389/fpubh.2022.923744
|View full text |Cite
|
Sign up to set email alerts
|

Disparities in the Prevalence of Childhood Obesity-Related Comorbidities: A Systematic Review

Abstract: BackgroundNon-communicable diseases among children are serious consequences of childhood obesity. However, less is known about the disparities in childhood obesity comorbidities burden. This review describes the salient pattern of disparities in the prevalence of childhood obesity-related non-communicable diseases and relevant inequalities in both high- and low/medium-income countries.MethodA systematic literature search was performed in MEDLINE, Embase, CINAHL, PsycInfo, Scopus, and Web of Science databases b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 130 publications
1
22
1
Order By: Relevance
“…In this review, a higher prevalence of MetS was found in girls than in boys, differing from that reported in the systematic review by Friend et al 53 with data from 2003 to 2010 and by Obita et al 54 who used information from 2010 to 2018; however, both include children and adolescents aged 2 to 18 years. However, these prevalences of MetS between boys and girls can vary due to the variable prevalence of obesity present in different countries.…”
Section: Discussioncontrasting
confidence: 76%
“…In this review, a higher prevalence of MetS was found in girls than in boys, differing from that reported in the systematic review by Friend et al 53 with data from 2003 to 2010 and by Obita et al 54 who used information from 2010 to 2018; however, both include children and adolescents aged 2 to 18 years. However, these prevalences of MetS between boys and girls can vary due to the variable prevalence of obesity present in different countries.…”
Section: Discussioncontrasting
confidence: 76%
“…A MASLD prevalence ranging from 45.0% to 52.1% has been estimated among children with obesity in Asia based on a systematic review of 27 articles. 33 Overall MASLD prevalence among youth under 21 years of age is estimated at 7% in Asia, regardless of diagnostic method, from a meta-analysis encompassing 74 studies worldwide. 34 In Korea, a study using 2009-2018 data from the Korea National Health and Nutrition Examination Survey (KNHANES) found that 9.6% of 6327 children aged 10-18 years had suspected MASLD based on the biological ALT threshold.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to a few US studies exploring the epidemiology of suspected MASLD among Asian/PI children and global reviews, the majority of findings on Asian/PI children come from individual countries in Asia where the estimated prevalence appears to be increasing. A MASLD prevalence ranging from 45.0% to 52.1% has been estimated among children with obesity in Asia based on a systematic review of 27 articles 33 . Overall MASLD prevalence among youth under 21 years of age is estimated at 7% in Asia, regardless of diagnostic method, from a meta‐analysis encompassing 74 studies worldwide 34 .…”
Section: Discussionmentioning
confidence: 99%
“…Some parents commented on the di culty of engaging their children in activities without the formality of a structured commitment with mentors and facilitators outside the family unit, reinforcing a common experience. Existing literature supports the bene cial effect on weight management of culturally tailored programs that program leaders directly supervise for the duration of the program [28,29]. Even though the group consensus favored the reimplementation of the FIT4YES program, multiple ideals instilled by the program remained intact, inspiring the continuation of healthy substitutions into meal-time recipes, activities around the neighborhood, and choosing to become more health-aware throughout daily life.…”
Section: Discussionmentioning
confidence: 99%